2009
DOI: 10.1002/cjoc.200990170
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Olaquindox Polyclonal Antibody

Abstract: 2-[N-(2-Hydroxyethyl)-carbamoyl]-3-methyl-oxoquinoxaline-1,4-oxides (OLA) was first mono-esterificated by succinic acid anhydride, and was then turned into a derivative with carboxyl. The synthetic product was purified by recrystallization with a yield of 52.47%. Its chemical structure was determined by NMR, IR and MS spectra. The determined structure was used to synthese OLA hapten, which had the molecular structural characteristics of OLA. The OLA hapten and bovine serum albumin (BSA) were conjugated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…[29][30][31][32][33] Poisoning incidents, even death, have occurred occasionally due to overdose of isoniazid (isonicotinic acid hydrazide, INH), which is a wonder drug for tuberculosis and is one of the top pharmaceuticals that has changed the world. [34][35][36][37][38] Therefore, controlling the dose of INH is very important to sufferers in clinical chemistry, which has prompted study of analytical methods for INH, including titrimetric, 39,40 colorimetric, [41][42][43] spectrophotometric, [44][45][46][47][48][49][50] atomic absorption spectrometric, 51 fluorimetric, [52][53][54] high performance liquid chromatographic, [55][56][57][58][59][60][61][62] capillary electrophoresis, 63,64 chromatographic, 65,66 mass spectrometric, 67 chemiluminescence, [68][69][70][71][72][73][74][75][76][77]…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] Poisoning incidents, even death, have occurred occasionally due to overdose of isoniazid (isonicotinic acid hydrazide, INH), which is a wonder drug for tuberculosis and is one of the top pharmaceuticals that has changed the world. [34][35][36][37][38] Therefore, controlling the dose of INH is very important to sufferers in clinical chemistry, which has prompted study of analytical methods for INH, including titrimetric, 39,40 colorimetric, [41][42][43] spectrophotometric, [44][45][46][47][48][49][50] atomic absorption spectrometric, 51 fluorimetric, [52][53][54] high performance liquid chromatographic, [55][56][57][58][59][60][61][62] capillary electrophoresis, 63,64 chromatographic, 65,66 mass spectrometric, 67 chemiluminescence, [68][69][70][71][72][73][74][75][76][77]…”
Section: Introductionmentioning
confidence: 99%
“…22 Immunoassays have been developed for OLA residue detection. 3,[23][24][25][26] However, few researchers have used monoclonal antibody based-ELISA for QCT and MEQ detection. The simultaneous detection of multi-residue quinoxaline antibiotics has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 SCUE has better solubilities and much more superior absolute bioavailability than SCU in vivo. 4 Recent reports disclosed that SCUE was the main metabolite of SCU when it was administered to rats. [5][6][7][8] Moreover, it was reported that SCUE had other important physio-and pharmacological activities such as preventing vascular endothelial dysfunction, 9 inhibiting the proliferation of human retinal endothelial cells (HREC), 10 inhibiting SARS-CoV (Severe acute respiratory syndrome-coronavirus), 11 decreasing neurological deficit score and cerebral infarction volume, 12 and selective cytotoxicities towards cancer cells.…”
mentioning
confidence: 99%